Pengembangan Video Based Learning Berbasis Objek Sejarah di Indragiri Hulu dalam Pembelajaran Sejarah Siswa SMAN 1 Batang Cenaku - Anggi Afrilianti; Bunari Bunari; Suroyo Suroyo (CHRONOLOGIA, 2022)
The development of video-based learning is carried out so that students do not feel bored while learning history and can more easily absorb or understand the material from the method. This improves the learning of local history in Indragiri Hulu which has teaching and noble historical values. The purpose of this research is to carry out innovation in the development of video-based learning media. This new learning media developed is expected to be able to support the increasing local historical knowledge of the students of SMA N 1 Batang Cenaku, especially in class X Social Sciences. The type of research used is research and development (R&D). The research sample amounted to 59 students who were students of class X SMAN 1 Batang Cenaku. The results showed that video-based learning based on historical objects in Indargiri Hulu in history learning was declared "very feasible" to be used.